Family gaps in income: A cross-national comparison - Wendy Sigle-Rushton; Jane Waldfogel (Luxembourg Income Study (LIS), 2004)
Using data on nine countries from the Luxembourg Income Study database, we estimate trajectories in gross and disposable family incomes for families following one of several stylized life-courses: marrying or partnering at age 24 but not having children; partnering at age 24 and having one child at age 27; partnering at age 24 and having two children, at ages 25 and 27; and partnering at age 24, having two children at ages 25 and 27, and then living without a partner from ages 30 to 39. Focusing mainly on women with a medium level of education, the majority of women in most of our countries, we find a clear clustering of countries. In general, family gaps in both gross and disposable family income are smallest in the Nordic countries, intermediate in the Anglo-American countries, and largest in the continental European countries. This clustering is very similar to patterns observed in the literature on family gaps in women's earnings and suggests that differences in earnings between women with different family histories are the major driver in the family gaps in gross and disposable incomes that we observe here.
Keywords: 330; Haushaltseinkommen; Familienleistungsausgleich; Kinder; Nordamerika; Europa; Australien